A STUDY OF CONVERTED-WAVE MODELING: ANALYSIS OF FACTORS THAT AFFECT THE P-S WAVE EXTRACTION QUALITY ON VERTICAL COMPONENT DATA - Christy Viony, Natashia
Converted-wave seismic method is able to provide better subsurface images in complex geological structures compared to conventional seismic methods. In the same P-waves frequency bandwidth, S-waves have shorter wavelength therefore their vertical resolution is higher than the P-waves and S-waves are not sensitive to the fluid therefore the attenuation and diffraction effects are less than the P-waves. However, the converted-wave survey needs large costs as it requires the multicomponent receiver. From the Zoeppritz equation (1919), the P-S waves energy can still be recorded on the vertical component, although generally the vertical component is dominated by the PP waves energy. Previous study proved the success of extracting P-S signals in seismic data from vertical components (Viony & Triyoso, 2018). However, this P-S extraction approach has limitations. In this study, the factors that affect the quality of P-S extraction from the vertical component are discussed and an analysis of the characteristics of P-P and P-S is performed in defining lithology and fluid. The synthetic data with shallow gas and salt intrusion is used in this study. The results showcase the P-S seismic section imaged the subsurface better than the P-P. The AVO P-P curve shows anomaly class 3, while the AVO P-S curve shows no anomaly. This is a positive conclusion about the existence of fluids if the AVO P-P and P-S curves show the opposite results. This is because S waves are not sensitive to the presence of fluids and purely describe lithology. However, P-S extraction did not provide an adequate image. From this study it was concluded that the factors affecting the quality of P-S extraction on vertical components include: configuration / layout of seismic data acquisition and contrast of Vp / Vs. Shooting configuration with the same receiver space as half of source space will result the empty CCP binning at several points and a high Vp / Vs ratio resulting the smaller P-S amplitude on the vertical component.